End-of-life health literacy, knowledge and behaviours towards advance care planning among older adults: cross-sectional evidence from Switzerland - Ralf J Jox; Maud Wieczorek; Clément Meier; Sarah Vilpert; Jürgen Maurer; Carmen Borrat-Besson (BMJ Publishing Group, 2024)
Introduction Population ageing, technological advancements and an increasing emphasis on patient empowerment imply that individuals are increasingly confronted with intricate end-of-life decisions. Personal end-of-life health literacy skills may help empower individuals to participate more actively in their own end-of-life decisions, including engagement in advance care planning (ACP). This study thus investigates the associations between individuals' end-of-life health literacy and their knowledge and behaviours toward ACP among a population-based sample of adults aged 58+ years in Switzerland.Methods We used data from 1319 respondents from Wave 8 (2019/2020) of the Survey on Health, Ageing, and Retirement in Europe. The Subjective End-of-life Health Literacy Scale (S-EOL-HLS) served as the measurement tool. Respondents' end-of-life knowledge was assessed using test-based questions about 11 end-of-life medical situations. Behaviours toward ACP were measured by whether respondents have discussed their end-of-life wishes, completed advance directives (AD) and appointed a potential surrogate for medical decisions in case of incapacity. Associations were estimated using separate ordinary least square and probit regressions, controlling for social, health and regional characteristics.Results Respondents with higher end-of-life health literacy tended to have better end-of-life knowledge and were more likely to have discussed their end-of-life wishes, to have completed AD and to have appointed a surrogate for medical decisions in case of incapacity. On regressing the outcomes on the three end-of-life health literacy dimensions, interactive health literacy positively correlated with end-of-life knowledge and the three behaviours toward ACP, while critical health literacy was only associated with having an AD and appointing a surrogate for medical decisions.Conclusions Our findings suggest that end-of-life health literacy may play a significant role in individuals' level of end-of-life knowledge and their behaviour toward ACP. Thus, developing public health policies that aim at strengthening their end-of-life health literacy skills may increase individuals' engagement in the ACP process and make ACP more effective.